C41. Emerging Pharmacology for Chronic Obstructive Pulmonary Disease: Mechanisms and Outcomes 2010
DOI: 10.1164/ajrccm-conference.2010.181.1_meetingabstracts.a4419
|View full text |Cite
|
Sign up to set email alerts
|

Dose Delivery Characterization Of Indacaterol Following Inhalation By COPD Patients

Abstract: Background and RationaleIndacaterol is an investigational, novel, inhaled once-daily long-acting β -agonist for the treatment of chronic obstructive pulmonary 2 disease (COPD). The therapeutic agent is administered as an inhalation dry powder using a new low resistance single dose dry powder inhaler (SDDPI) which will be known as Breezhaler® when approved in Europe. The aim of the present study was to investigate the in vitro dose delivery performance of indacaterol under a range of inspiratory flow rate condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Due to its low intrinsic internal resistance it requires high inspiratory flow rates (100 and 117 L/min) to obtain a mean pressure drop of 4 kPa within the device [27]. However, Pavkov et al [28] and Singh et al [29] have shown that COPD patients are able to generate a peak inspiratory airflow of approximately 90 L/min through the Breezhaler device, overcoming a pressure drop of approximately 3 kPa. Although performance of DPIs are usually compared at 4 kPa pressure drop [26], studies in COPD patients demonstrated consistent dose delivery from Breezhaler using flow rates between 50 and 100 L/min [28,30] corresponding to a pressure drop less than 4 kPa.…”
Section: Breezhaler ® : An Example Of Recent Capsule-based Dpimentioning
confidence: 99%
“…Due to its low intrinsic internal resistance it requires high inspiratory flow rates (100 and 117 L/min) to obtain a mean pressure drop of 4 kPa within the device [27]. However, Pavkov et al [28] and Singh et al [29] have shown that COPD patients are able to generate a peak inspiratory airflow of approximately 90 L/min through the Breezhaler device, overcoming a pressure drop of approximately 3 kPa. Although performance of DPIs are usually compared at 4 kPa pressure drop [26], studies in COPD patients demonstrated consistent dose delivery from Breezhaler using flow rates between 50 and 100 L/min [28,30] corresponding to a pressure drop less than 4 kPa.…”
Section: Breezhaler ® : An Example Of Recent Capsule-based Dpimentioning
confidence: 99%
“…Because of its low characteristic inner opposition it requires high inspiratory stream rates (100 and 117 L/min) to acquire a mean weight drop of 4 kPa inside the gadget [27]. Be that as it may, Pavkov et al [28] and Singh et al [29] have indicated that COPD patients can produce a pinnacle inspiratory wind stream of roughly 90 L/min through the Breezhaler gadget, conquering a weight drop of around 3 kPa. In spite of the fact that presentation of DPIs are generally thought about at 4 kPa pressure drop [26], concentrates in COPD patients exhibited predictable portion conveyance from Breezhaler utilizing stream rates somewhere in the range of 50 and 100 L/min [28,30] comparing to a weight drop under 4 kPa.…”
Section: Breezhaler®: An Example Of Recent Capsule-based Dpimentioning
confidence: 99%
“…Potwierdzono, że nowe urządzenie podające cząsteczki indakaterolu SD-DPI zapewnia stałą dobrą depozycję leku niezależnie od stopnia ciężkości POChP [11]. Wyniki badania INLIGHT 2, randomizowanego, podwójnie zaślepionego, prowadzonego w grupach równoległych u 1000 chorych na POChP wykazały, że chorzy, którzy otrzymywali 150 µg indakaterolu mieli po 6 miesiącach obserwacji mniej nasiloną duszność, większy efekt rozkurczowy.…”
Section: Nowe Leki Z Grupy Ultra-labaunclassified